2001
DOI: 10.1007/s004390100554
|View full text |Cite
|
Sign up to set email alerts
|

Genetic basis of mitochondrial HMG-CoA synthase deficiency

Abstract: Deficiency of mitochondrial 3-hydroxy-3-methylglutaryl-CoA synthase (mHMGS) is a recessive disorder of ketogenesis that has been previously diagnosed in two children with hypoglycaemic hypoketotic coma during fasting periods. Here, we report the results of molecular investigations in a third patient affected by this disease. Sequencing of the entire coding region of the HMGCS2 gene revealed two missense mutations, G212R and R500H. Mendelian inheritance was confirmed by the analysis of parental samples and neit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 11 publications
(15 reference statements)
3
40
1
Order By: Relevance
“…Variations in the genes encoding ketogenic mediators, including HMGCS2, HMG-CoA lyase, and βOHB dehydrogenase, have not yet emerged as independent predictors of liver pathology or diabetes. While HMGCS2 deficiency is very rare in humans, total HMGCS2 enzymatic deficiency is associated with pediatric hypoketonemic hypoglycemia and hepatic steatosis (66)(67)(68)(69)(70)(71). Importantly, our studies of neonatal mice revealed that partial loss of HMGCS2 activity caused marked hepatic steatosis vastly out of proportion to the diminution in neonatal ketosis, but did not result in neonatal hypoglycemia or failure to thrive.…”
Section: Discussionmentioning
confidence: 73%
“…Variations in the genes encoding ketogenic mediators, including HMGCS2, HMG-CoA lyase, and βOHB dehydrogenase, have not yet emerged as independent predictors of liver pathology or diabetes. While HMGCS2 deficiency is very rare in humans, total HMGCS2 enzymatic deficiency is associated with pediatric hypoketonemic hypoglycemia and hepatic steatosis (66)(67)(68)(69)(70)(71). Importantly, our studies of neonatal mice revealed that partial loss of HMGCS2 activity caused marked hepatic steatosis vastly out of proportion to the diminution in neonatal ketosis, but did not result in neonatal hypoglycemia or failure to thrive.…”
Section: Discussionmentioning
confidence: 73%
“…The GO terms included genes for carnitine palmitoyltransferase I ( CPT1 ), 3‐hydroxy‐3‐methylglutaryl‐coenzyme A (CoA) synthase 2 ( HMGCS2 ), and 3‐oxoacid CoA‐transferase 1 ( OXCT1 ), which are known to play important roles in generating energy in cells and tissues 13, 14, 15…”
Section: Resultsmentioning
confidence: 99%
“…The KEGG pathway analysis showed that the genes related to butanoate metabolism were down‐regulated in the thin endometrium. Genes, such as CPT1 , HMGCS2 , and OXCT1 , are essential for generating acetyl‐CoA and ketone bodies in butanoate metabolism 13, 14, 15. Butanoate is a substrate that is used to generate energy in both aerobic and anaerobic processes.…”
Section: Discussionmentioning
confidence: 99%
“…Case reports indicate that HMGCS2-and SCOT-deficient humans adapt poorly to nutrient states that are marked by diminished carbohydrate intake. Human HMGCS2 deficiency results in pediatric hypoketonemic hypoglycemia (42), and human CoA transferase deficiency manifests as spontaneous pediatric ketoacidosis (43,44), which in severe cases is associated with hypoglycemia and may account for a subset of idiopathic ketotic hyopoglycemia cases (45,46). SCOT-KO mice die in a manner that mimics human sudden infant death syndrome (SIDS)/sudden unexpected death in infancy (SUDI), the leading cause of death of U.S. infants after the age of 1 month (47).…”
Section: Discussionmentioning
confidence: 99%